Podatkowe instrumenty wspierania działalności innowacyjnej w Polsce i innych krajach Unii Europejskiej - Rękas, Magdalena (Tax Instruments in Support of Innovation Performance in Poland and Other EU Countries, 2008)
In the latest edition of the annual assessment of the EU members innovation performance, European Innovation Scoreboard 2006, Comparative Analysis of innovation Performance, the Polish economy was ranked 251st among the EU, Japan, and the USA, ahead of just Turkey, Romania, Bulgaria, and Greece. The rating shows the scale of problems that the Polish economy faces in the sphere of innovation performance. Establishing a complex national policy to facilitate covering the distance between our businesses and the European average seems to be both a necessity and a challenging task. An important factor is also creation of local tax solutions in support of innovations. The article briefly compares the levels of R&D expenditure in Poland and in selected countries of the world. It then goes on to present the tax solutions applied in Poland for innovation support. The article concludes with a preliminary evaluation of the introduced changes against the current economic knowledge.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 2, s. 11-21